Very best (almost) friends poems of friendship - Janeczko, Paul B.; Davenier, Christine (Cambridge, Mass. : Candlewick Press, 1999)
A collection of poems celebrating the good and bad things about friendship, giving, loneliness, and love, by such authors as Myra Cohn Livingston, John Ciardi, and Gwendolyn Brooks.
8 - 10 years
Keywords: Friendship -- Juvenile poetry; Children's poetry, American; Friendship -- Poetry; American poetry -- Collections